Amyotrophic Lateral Sclerosis, a Multisystem Pathology: Insights into the Role of TNFα - Massimo Tortarolo; Daniele Lo Coco; Pietro Veglianese; Antonio Vallarola; Maria Teresa Giordana; Gabriella Marcon; Ettore Beghi; Marco Poloni; Michael J. Strong; Anand M. Iyer; Eleonora Aronica; Caterina Bendotti (Mediators of Inflammation)
Amyotrophic lateral sclerosis (ALS) is considered a multifactorial, multisystem disease in which inflammation and the immune system play important roles in development and progression. The pleiotropic cytokine TNFα is one of the major players governing the inflammation in the central nervous system and peripheral districts such as the neuromuscular and immune system. Changes in TNFα levels are reported in blood, cerebrospinal fluid, and nerve tissues of ALS patients and animal models. However, whether they play a detrimental or protective role on the disease progression is still not clear. Our group and others have recently reported opposite involvements of TNFR1 and TNFR2 in motor neuron death. TNFR2 mediates TNFα toxic effects on these neurons presumably through the activation of MAP kinase-related pathways. On the other hand, TNFR2 regulates the function and proliferation of regulatory T cells (Treg) whose expression is inversely correlated with the disease progression rate in ALS patients. In addition, TNFα is considered a procachectic factor with a direct catabolic effect on skeletal muscles, causing wasting. We review and discuss the role of TNFα in ALS in the light of its multisystem nature.